Characterization of the fruit proteolytic system of Bromelia serra Griseb. (Bromeliaceae) and its application in bioactive peptides release - Salese, Lucía (2022)
A crude extract with proteolytic activity was prepared from edible fruits of Bromelia serra, containing cysteine peptidases with molecular masses between 24.1 and 25.9 kDa. The extract presented an optimal pH range of 6.03‒9.05, retained more than 80% of activity after thermal pre-treatments at 23, 37, and 45°C (120 min), but it was rapidly inactivated after 10 min at 75°C. These proteases were employed to hydrolyze soybean proteins, bovine casein and bovine whey, achieving degrees of hydrolysis of 18.3 ± 0.6, 29.1 ± 0.7, and 12.6 ± 0.9% (55°C, 180 min), respectively. The casein 180 min-hydrolysate (55°C) presented the maximum value of antioxidant activity (2.89 ± 0.12 mg/mL Trolox), and the whey protein 180 min-hydrolysate (55°C) showed the highest percentage of angiotensin-converting enzyme inhibition (91.9 ± 1.2%). This low-cost enzymatic preparation would be promising for the food industry because it requires mild working conditions and yields hydrolysates with biological activities useful as ingredients for functional food. Practical application: Proteolytic enzymes are employed in the food industry in a wide variety of processes since they modify the properties of proteins causing beneficial effects such as improvement digestibility, diminution of allergenicity, and release of bioactive peptides. Fruits from Bromelia serra possess cysteine peptidases that could be used in food biotechnology because they are capable to hydrolyze soybean and milk proteins by mild working conditions and to provoke the release of bioactive peptides. These hydrolysates containing antioxidative and ACE-inhibitor activities would be useful as ingredients for functional foods or as nutraceuticals, which are nowadays two products highly required by consumers.